Designing sustainable colour : lowering the environmental impact during the wool dyeing process : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Harman, Rebekah (Massey University, 2013)
Synthetic dyeing has been used in the production of coloured textiles since the late 1800s. However, today there is growing awareness that the dyeing process has a huge impact on the environment, causing damage to the earth’s climate from high carbon emissions and damage to ecology through discharge of toxic wastewater. Carpets and Rugs of New Zealand Limited (CRONZ) is a small manufacturer of bespoke tufted carpet based in Christchurch, New Zealand who wanted to help combat these environmental problems by offering a sustainable dyeing process as part of their business. They applied for and successfully gained Ministry for Science and Innovation funding for a postgraduate student fellowship to enable this project. The methods of life cycle analysis, traceability, sustainable certification and labelling, along with running many small-scale experiments, including exploration of the new technology of ultrasound waves in the dye bath, are used here to discover strategies to lower energy and chemical use during the hank dyeing process for wool yarns. By gaining an understanding of the hank dyeing process for wool yarns through interviews with industry experts, and documenting energy and chemical use during experiments, the following key solutions for reducing energy and chemical use were found: reducing dye bath time by dyeing lighter colours, as these process faster than dark colours; use of eco-friendly chemicals that do not contain harmful heavy metals; use of agitation of the dye bath as a method to produce level colour, eliminating the need for a chemical levelling agent; and the use of blended un-dyed yarns as an alternative to dyeing the wool fibres. By employing solutions such as these the carpet manufacturing industry would lessen its environmental impact by lowering carbon emissions and discharging fewer chemicals into wastewater streams.
Keywords: Dyes and dyeing and the environment; Coloured textile production; Carpet industry; Sustainable dyeing process; Wool dyes